Evidences, codes and classifications: the historian’s craft and the digital world - Fortes, Alexandre (2020)
This article examines the impact of the global diffusion of digital technologies on the historian’s craft. It is based on an analysis of the linkage between the praxis of the profession and the nature of historical knowledge as stated by some of the greatest historians of the 20th Century. It examines the social nature of language and its role in the constitution of evidences and historical sources, and draws connections between this analysis and the technological advances of “natural language processing”. Is discusses concepts from various branches of the social sciences that are relevant for understanding the developmental process of human knowledge and the role of information codification in the construction of historical narratives. Finally, it presents an overview of the main methodologies in the field of artificial intelligence currently applied to historical research.